PENGARUH BADAN USAHA MILIK DESA (BUMDES) DALAM MEMBERDAYAKAN MASYARAKAT MELALUI PETERNAKAN AYAM PETELUR - Muhammad Syabil Rabbani; Asep Samsudin; Anita Rakhman (Comm-Edu (Community Education Journal), 2026)
This study explores the influence of Village-Owned Enterprises (Badan Usaha Milik Desa/BUMDes) in empowering rural communities through layer chicken farming in Giriasih Village, Batujajar District, West Bandung Regency. The research aims to analyze the impact of BUMDes on economic and social empowerment, the supporting and inhibiting factors, and the process of community empowerment through livestock activities. Employing a mixed-method approach with an explanatory sequential design, the research combined quantitative questionnaires (Likert scale) distributed to community members with qualitative data collected through in-depth interviews, observation, and documentation. The findings reveal that BUMDes significantly contributes to improving community welfare by providing training, funding, and operational support in poultry farming. Key supporting factors include strong community participation and available local resources, while inhibiting factors involve limited capital, fluctuating feed prices, and lack of managerial skills. The process of empowerment through BUMDes is manifested in collective planning, skill development, and enhanced community independence in agribusiness management. The study concludes that BUMDes plays a crucial role in fostering self-reliance, economic resilience, and sustainable rural development.